The Influence of Work Engagement and Perceived Organizational Support on Organizational Commitment with Job Burnout as a Moderating Variable among Teachers and Education Staff at Binekas Elementary School, Bandung - Rachmi Silviana; Neuneung Ratna Hayati (Dinasti Publisher, 2025)
This study investigates the influence of work engagement (WE) and perceived organizational support (POS) on organizational commitment (OC), with job burnout (JB) as a moderating variable, among teachers and educational staff at Binekas Elementary School, Bandung. Employing a quantitative-verificative approach with a survey method, data from 60 respondents were analyzed using Moderated Multiple Regression (MMR). The first model demonstrated that WE significantly predicts OC (? = 0.602, p = 0.012), whereas POS was not statistically significant (? = 0.368, p = 0.063). JB did not have a significant direct effect on OC (? = –0.175, p = 0.404). In the second model, the interaction effects between WE and JB (? = 0.015, p = 0.671), as well as between POS and JB (? = 0.016, p = 0.705), were found to be insignificant, indicating that job burnout does not moderate the relationship between WE or POS and OC. The R² change between models was minimal (?R² = 0.008; p = 0.732), further confirming the non-significant moderating effect. These findings highlight the robust role of work engagement in enhancing organizational commitment, while the influence of POS and job burnout remains statistically unsupported within this context.